SUPPLY AND DEMAND OF FISH IN BOSNIA AND HERZEGOVINA - Jalić, Nemanja; Ostojić, Aleksandar; Savić, Nebojša (Economics of Agriculture, 2022)
The primary goal of the paper was to analyze the fish market of Bosnia and Herzegovina (B&H). The paper presents the level of self-sufficiency and import dependence of fish for the period 2014-2020. The source of data was the data of the B&H Agency for Statistics and Indirect Taxation Authority of B&H. The following methods were applied: descriptive statistics, trend data and balance sheet method. On average, 3.161 tons of trout were produced in B&H per year, 82% of total fish production. Carp were produced 510 tons per year. Other freshwater fish are becoming less and less attractive for production. B&H’s fish self-sufficiency is low (54%) and the average rate of import dependence is about 76%. The consumption of fish per capita is 2 kilograms. It is necessary to improve the education of the population throughout B&H about the importance of fish nutrition and the health aspects of its consumption.